Immune tolerance induction with moroctocog‐alpha (Refacto/Refacto AF) in a population of Italian haemophilia A patients with high‐titre inhibitors: Data from REF.IT Registry. Issue 6 (11th October 2019) - Zanon, Ezio; Pasca, Samantha; Pollio, Berardino; Santagostino, Elena; Linari, Silvia; Tagliaferri, Annarita; Santoro, Cristina; Rocino, Angiola; Marino, Renato; Aru, Brigida; Borchiellini, Alessandra; Siragusa, Sergio; et al.
Abstract: Background: The appearance of inhibitors is the most serious complication in haemophilia A (HA) patients. The primary objective is their eradication. Up to date, immune tolerance induction (ITI) was the only therapeutic option to achieve this. Aim: To assess the efficacy of moroctocog‐alpha as an ITI regimen in a population of HA patients with high‐titre inhibitors. Methods: The REF.IT Registry is a retrospective‐prospective study that collected data on all patients with HA and high‐titre inhibitors treated with moroctocog‐alpha as an ITI regimen at twelve Italian Haemophilia Centres. Results: We enrolled 27 patients, 85.2% were children. All patients were high responders, 88.9% had severe HA. We found 69.3% of them had one or more risk factors for poor ITI prognosis, 14.8% were ITI rescue. Overall 59.3% achieved a complete/partial success (complete in 51.9%). ITI failed in 11 patients, 63.6% of them with poor‐prognosis risk factors. Inhibitors appeared after a mean of 27 exposure days. Mean historical peak was 78.8 BU/mL. The primary ITIs started on average 20.2 months after the diagnosis. A partial or complete success after a mean of 15 months of treatment was achieved in 56.6% of the children while the same result was obtained by 75.0% adults after 22 months from ITI onset. Patients who were treated with high‐dose moroctocog‐alpha (200 UI/kg/day) were 63.0%. Conclusion: Our Registry showed that the use of moroctocog‐alpha in the setting of ITI was effective and safe also in a population of patients with high‐titre inhibitors, presenting one or more risk factors for poor ITI prognosis.